Ordinances, Rules and Regulations of the Department of Parks of the City of New York 7 (1916). - (:unkn) unknown (My University, 1916)
No person shall, in any park, . . . 8. Fire or carry any firearm, firecracker, torpedo or fireworks.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE; SENSITIVE PLACES